Skills training for work in rail industry - Joash EE, De Silva (The Star Publications (M) Berhad, 2017)
KUANTAN: The East Coast Rail Link (ECRL) Industrial Skills Training Programme (PLKI-ECRL) is hoping the get 3,600 trainees on board by 2022 to improve their skills and experience in the rail industry.